Horace Odes 1.24: Quintilius and Epicureanism, Philodemus and Varius - Cairns, Francis (Classica et Mediaevalia, 2025)
A number of Epicurean elements have been identified in Odes 1.24 by past scholarship. This paper begins by summarising them, before proposing two major additions, one a quotation from Philodemus On Death. A final section appends a speculation about another possible Epicurean source for the ode, Varius’ De Morte.